Efavirenz-induced urolithiasis. - Wirth, G; Teuscher, J; Graf, J; Iselin, C (2006)
We describe the first case of efavirenz-induced urolithiasis in a 47-year-old HIV-positive patient. Urinary obstruction led to pyelonephritis and septic shock, requiring emergency ureteral catheterisation. The subsequent clinical course was favourable, allowing the patient's discharge on day 5. A 7 mm, radio-translucent, non-crystalline, beige stone was extracted during catheterisation. Stone analysis by Fourier transform infrared spectrometry, liquid chromatography and mass spectrometry revealed a stone composed of efavirenz (EFV) metabolites M4, M5, M8 (as described by Mutlib et al. in 1999) and approximately 50% of unspecified proteins. EFV is a non-nucleoside reverse transcriptase inhibitor introduced to European markets in 1999. It is principally metabolised by cytochrome P450 3A4 and 2B6. Of the dose, 14-34% is excreted in the urine, 1% as unchanged drug. The patient had been taking 600 mg EFV per day for 3 years. As EFV-induced urolithiasis has not been reported so far, we would like to draw the attention of the medical community to this potentially severe complication.